Age and genesis of the Gangcha gold deposit, western Qinling orogen, China. (17th October 2017) - Kong, Chi Seng; Shen, Junfeng; Santosh, M.; Li, Shengrong; Cao, Weidong; Peng, Zidong; Liu, Haiming; Li, Jinchun; Li, Jie; Bao, Lin
Abstract : The Gangcha gold deposit in Hezuo, Gansu, China, is a newly discovered medium‐scale (19 tons) epithermal deposit occurring within the western Qinling orogenic belt. The Daguanshan Formation, represented by metamorphosed volcanic–clastic rock suite, is the main ore‐bearing strata. Gold occurs mainly as submicroscopic inclusions in sulphides and quartz. The hydrothermal alteration is characterized by mid‐ to low‐temperature mineral assemblages such as pyrite, arsenopyrite, and fluorspar. We report results from Rb–Sr isotopic dating of pyrites in the main orebody, which yield an isochron age of 225.3 ± 3.4 to 229.9 ± 4.7 Ma suggesting that the mineral deposit formed during the middle Triassic within a collisional orogenic setting. The initial 87 Sr/ 86 Sr value of pyrite (0.710326 to 0.710349) is lower than that of the continental crust and higher than that of the mantle. The S isotope data of pyrites from the deposit show a narrow range from 0.6‰ to 1.3‰ with an average of 0.975‰. Their Pb isotopes exhibit characteristics of a crust–mantle mixed source with a μ ( 238 U/ 204 Pb) of 9.39 to 9.53 and a ω ( 232 Th/ 204 Pb) of 36.81 to 38.14. The S and Pb isotopic composition indicates that ore‐forming materials were derived from a magma sourced in the lower crust, which also incorporated mantle components.